Actualization of the concept of "Russian idea" within the framework of the paradigm of Russian civilizational statehood - Evgeniya I. Stebunova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. To comprehend modern global trends in the paradigm of Russia's relations with the world requires the actualization of the concept ‘Russian idea’. For this purpose, the article makes a selective socio-philosophical analysis of the process of evolution of the concept ‘Russian idea’ from the early twentieth century to the present day within the cultural-historical paradigm.